JIHAD DAN TOLERANSI DALAM RISALAH ASWAJA;RESPON NAHDAHATUL ULAMA TERHADAP NARASI KEKERASAN BERBASIS AGAMA DI MEDIA SOSIAL - Elsa Amelia Ahsana (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
This study aims to examine jihad and tolerance in the Risalah Aswaja (The Message of the Prophet Muhammad), the Nahdlatul Ulama (NU)'s response to narratives of religious-based violence on social media.The concept of jihad in the Risalah Aswaja is broadly understood as peace and the preservation of communal harmony in accordance with the teachings of Islam. This article also highlights the value of tolerance in the Risalah Aswaja, which prioritizes respect between religious communities and a commitment to maintaining unity through dialogue and deliberation. In the era of social media, Nahdlatul Ulama (NU) plays an active role in countering narratives of religious-based violence with a moderate, educational, and inclusive da'wah approach to strengthen religious moderation and prevent social conflict. The research in this article uses normative legal research methods with a phenomenological approach. It can be concluded that the Risalah Aswaja serves as a foundation for Nahdlatul Ulama's thinking in facing the challenges of religious-based violence in the digital age. By emphasizing the non-violent meaning of jihad and promoting tolerance, NU has succeeded in constructing a narrative that strengthens unity and prevents the spread of dangerous ideologies.